Low-income Childless Young Adults’ Marriage and Fertility Frameworks - Rackin, Heather M (J Marriage Fam, 2017)
We investigate how low-income young adults without children understand marriage and fertility. Data come from the Becoming Partners and Parents Study (N=69) a qualitative study of African-American adults ages 18-22 in a midsize southern city. This is the first study to analyze young, low-income, childless and unmarried Black respondents’ frameworks (i.e., internal understandings of the world) of marriage and fertility. In contrast to research conducted on parents, our research on childless adults indicated a narrative in which there were close connections between marriage and fertility and an economic-bar adhered to both marriage and childbearing. Respondents also believed that childbearing was meaningful and provided purpose, but that it was morally questionable if the parent was not financially stable. Our results suggest that prior findings related to meanings of family formation and childbearing for low-income parents may not extend to those without children.